Mutation Breeding and Efficiency Enhancing Technologies for Resistance to Striga in Cereals - Ghanim, Abdelbagi M. A.; Sivasankar, Shoba; Rich, Patrick J. (Springer Berlin Heidelberg : Imprint: Springer, 2024)
This open access book is a compilation of protocols developed through a Coordinated Research Project of the Joint FAO/IAEA Center of Nuclear Techniques in Food and Agriculture, specifically focused on mutation breeding for resistance to Striga. The book consists of three sections; (i) a general introduction on Striga biology and impact and mutagenesis in cereal crops; (ii) protocol chapters focusing on field, screenhouse and laboratory screening and diagnostic for resistance to Striga asiatica and S. hermonthica in sorghum, upland rice and maize, and; (iii) efficiency enhancing technologies such as rapid crop cycling, doubled haploid production and genomics for mutation discovery and marker development. These chapters were written by well recognized experts in Striga biology and physiology, and cereal breeders. The book is intended to serve as a unique reference and guide for plant breeders and geneticists engaged in breeding for resistance to Striga in cereals.